Evaluation of Customer Satisfaction with Railway Company Services in Area VI Yogyakarta - Indriyati Indriyati; Sarinah Sihombing; Lut Mafrudoh; Andre Yosafat; Euis Saribanon (Dinasti Publisher, 2025)
This study evaluates customer satisfaction with the service facilities of PT Kereta Commuter Indonesia (KCI) in Area VI Yogyakarta. As the number of Commuter Line (KRL) users continues to grow, understanding customer needs and expectations is crucial for improving service quality. A quantitative survey approach was employed using a Likert scale and multiple customer satisfaction measurement tools, including the Customer Satisfaction Index (CSI), Net Promoter Score (NPS), and Importance–Performance Analysis (IPA). The findings reveal that the CSI score reached 86.50%, indicating a high level of customer satisfaction, although several service dimensions particularly schedule punctuality and facilities for persons with disabilities still require improvement. To the best of the authors' knowledge, this is one of the first studies focusing on customer satisfaction in Area VI Yogyakarta that integrates CSI, NPS, and IPA simultaneously. The results provide valuable insights for PT KCI in formulating customer-centric service improvement strategies to further enhance overall satisfaction and service performance.